The study of psychophysiological indicators of students to the process of adaptation in the educational process (Experimental biology, 2018)
Despite the fact that adaptation to the conditions of the educational process among students of higher educational institutions is associated with psycho-physiological possibilities, as a whole, the individual features of adaptation have not been investigated. Therefore, the creation of informative psycho-physiological criteria for evaluation and forecasting of adaptation to educational loads, moreover, the study of the influence of social and biomedical environmental complex factors are very important. The purpose of research: the study of psycho-physiological indicators of students adapting to the learning processes. The research was conducted at the Kazakh National University named after al-Farabi, at the Department of Biophysics and Biomedicine of Biological Faculty. In this study 140 students were participated, 68 of them first-year students, 72 third-year students. The research was conducted in two groups: 1 group- first-year students, 2 group- third-year students. Research task: determination of students temperament ; revealing the level of emotional stress of students adapting to the learning processes; determination of the stressful state features; determination of emotional labiality in a stressful situation and the level of self-control; studying the empathic level of students. The conclusion of psycho-physiological research work conducted on first-year and third-year students is the adaptation of the third-year students to the learning processes, while among first-year students high emotional states indicating high neuro-emotional loads were determined.           Key words: adaptation, emotion, psychophysiology, stress, temperament, empathy.